Evaluation Of Penataran Train Fares During The COVID-19 Pandemic Using Atp-Wtp Methods - Achmad Wicaksono; Nur Aldi Firmansyah; Muhammad Ruslin Anwar (Rekayasa Sipil, 2022)
Indonesian Railways Company must increase the fare for the Penataran Train due to additional operational costs in providing the COVID-19 health protocol. On the other hand, people experience a reduction in monthly income due to the lack of activities outside the home. Ticket prices must be adjusted to determine the number of subsidies borne by the government. This study aims to evaluate the fare of the Penataran Train using the Ability To Pay (ATP) and Willingness To Pay (WTP) methods. Questionnaires have been distributed to 417 respondents using the Google Form application. The results showed that the ATP was higher than the WTP 1 without passenger expectations, and the ATP was lower than the WTP 2 with passenger expectations. Restriction of seating capacity is the most expected service by respondents. The recommended fare is IDR 33,478.00/trip, and the public service obligation is IDR 54,816.00/trip.